2016
DOI: 10.1158/1538-7445.am2016-lb-347
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-347: Ang-2/VEGF bispecific antibody reprograms macrophages and resident microglia to anti-tumor phenotype and prolongs glioblastoma survival

Abstract: OBJECTIVE: We aimed to enhance the efficacy of anti-VEGF therapy in glioblastoma (GBM) through additional inhibition of Angiopoietin-2 (Ang-2), a potential mediator of resistance to antiangiogenic therapy using VEGF inhibition. INTRODUCTION: Glioblastoma (GBM) is a uniformly lethal primary brain tumor affecting more than 12.000 patients every year in the US alone. The standard therapy regimen for this highly angiogenic tumor entity comprises maximal safe resection and chemoradiation with temozol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In addition to showing strong anti-tumor, antiangiogenic, and micrometastasis growth reducing effects in subcutaneous and orthotopic syngeneic mouse xenotransplantations, Ang-2-VEGF CrossMab also exhibits these effects in patient or cell linederived humanized tumor xenografts with acceptable side effects compared to Ang-1 inhibition combined with anti-VEGF treatment on physiologic vessel growth (103). Furthermore, Kloepper, Riedemann et al found that dual Ang-2/VEGF (CrossMab, A2V) antibody can prolong the survival of mice bearing orthotopic syngeneic (Gl261) GBMs or human (MGG8) GBM xenografts based on only VEGF pathway blocking failing to enhance overall survival of patients with GBM (104). The logical combination therapy of immune checkpoints and angiogenesis provides greater therapeutic effects, according to Schmittnaegel et al On the other hand, increased intratumoral immune effector cell activation results in increased PD-L1 expression in tumoral endothelial cells (105).…”
Section: Bispecific Antibody Targeting Non-immune Cells In the Tme Fo...mentioning
confidence: 99%
“…In addition to showing strong anti-tumor, antiangiogenic, and micrometastasis growth reducing effects in subcutaneous and orthotopic syngeneic mouse xenotransplantations, Ang-2-VEGF CrossMab also exhibits these effects in patient or cell linederived humanized tumor xenografts with acceptable side effects compared to Ang-1 inhibition combined with anti-VEGF treatment on physiologic vessel growth (103). Furthermore, Kloepper, Riedemann et al found that dual Ang-2/VEGF (CrossMab, A2V) antibody can prolong the survival of mice bearing orthotopic syngeneic (Gl261) GBMs or human (MGG8) GBM xenografts based on only VEGF pathway blocking failing to enhance overall survival of patients with GBM (104). The logical combination therapy of immune checkpoints and angiogenesis provides greater therapeutic effects, according to Schmittnaegel et al On the other hand, increased intratumoral immune effector cell activation results in increased PD-L1 expression in tumoral endothelial cells (105).…”
Section: Bispecific Antibody Targeting Non-immune Cells In the Tme Fo...mentioning
confidence: 99%
“…ABTAA favorably resulted in immune reprogramming in tumors, implying that simultaneous Tie-2 activation and Ang-2 suppression potently confer a favorable TME to facilitate the delivery of chemotherapeutic drugs into tumors (151). Furthermore, Jain and co-workers treated glioblastoma-bearing mice with antibodies targeting Ang-2/VEGF (CrossMab, A2V), and found that A2V attenuated microvascular density and polarized M2-like TAMs toward the anti-tumoral M1-like TAMs, leading to the retardation of tumor progression (152).…”
Section: Regulating Pericyte Coveragementioning
confidence: 99%
“…Kloepper et al have found that A2V, the ANG-2/VEGF cross-monoclonal antibody, reprograms protumor M2 macrophages toward the antitumor M1 phenotype in Gl261 and MGG8 glioblastoma models. They have shown that A2V may prolong survival in mice with GBM by reprogramming TAMs (Kloepper et al, 2016;Peterson et al, 2016). (Cook et al, 2016).…”
Section: Ang-2 Receptor Inhibitorsmentioning
confidence: 99%
“…Tumor-derived ANG-2 stimulates TIE2expressing monocytes/macrophages to exhibit a broader, tumor-promoting phenotype by binding to the ANG-1 receptor, a tyrosine kinase receptor(Coffelt et al, 2010).Kloepper et al have found that A2V, the ANG-2/VEGF cross-monoclonal antibody, reprograms protumor M2 macrophages toward the antitumor M1 phenotype in Gl261 and MGG8 glioblastoma models. They have shown that A2V may prolong survival in mice with GBM by reprogramming TAMs(Kloepper et al, 2016;Peterson et al, 2016).1.13 | Inhibition of HDACs HDACs serve as removing the acetyl groups on histones, a crucial step in epigenetic-regulating gene expression. HDAC family is composed of 18 proteins in mammals, which are divided into four classes (Class I, II, III, and IV).…”
mentioning
confidence: 99%